2021
DOI: 10.1183/13993003.00955-2020
|View full text |Cite
|
Sign up to set email alerts
|

Increased bactericidal activity but dose-limiting intolerability at 50 mg·kg−1 rifampicin

Abstract: Accumulating data have indicated that higher rifampicin doses are more effective and shorten tuberculosis treatment duration. This study evaluated the safety, tolerability, pharmacokinetics, and 7 and 14-day early bactericidal activity (EBA) of increasing doses of rifampicin. Here we report the results of the final cohorts of PanACEA HIGHRIF1, a dose-escalation study in treatment-naive adult smear-positive patients with tuberculosis. Patients received, in consecutive cohorts, 40 or 50 mg·kg−1 rifampicin once d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 26 publications
(48 reference statements)
1
32
1
Order By: Relevance
“…To help design such studies, simulations were conducted for widely available dosages of each drug, with the highest median being 34 mg/kg of rifampin, 17 mg/kg of isoniazid, 57 mg/kg of pyrazinamide, and 45 mg/kg of ethambutol. Recent trials have demonstrated a tolerable use of higher doses of rifampin up to 40 mg/kg in pulmonary TB patients with mild to moderate related adverse effects [ 28 , 29 , 30 ]. Similarly, patients treated with higher isoniazid doses between 15 and 20 mg/kg have had improved outcomes with faster culture conversion in rifampin-resistant anti-TB regimens [ 31 ], yet the essentiality of isoniazid has been more difficult to demonstrate for rifampin-susceptible TB [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To help design such studies, simulations were conducted for widely available dosages of each drug, with the highest median being 34 mg/kg of rifampin, 17 mg/kg of isoniazid, 57 mg/kg of pyrazinamide, and 45 mg/kg of ethambutol. Recent trials have demonstrated a tolerable use of higher doses of rifampin up to 40 mg/kg in pulmonary TB patients with mild to moderate related adverse effects [ 28 , 29 , 30 ]. Similarly, patients treated with higher isoniazid doses between 15 and 20 mg/kg have had improved outcomes with faster culture conversion in rifampin-resistant anti-TB regimens [ 31 ], yet the essentiality of isoniazid has been more difficult to demonstrate for rifampin-susceptible TB [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Rifampicin 40 mg/kg was recently identified as the highest tolerated dose with dose limiting factors reported as gastrointestinal disorders, pruritus, hyperbilirubinaemia and jaundice. 26 However, the safety of simultaneously administered high-dose pyrazinamide and rifampicin remains to be explored. Our study aims to investigate PK-PD data, safety and tolerability of a 4-month first-line treatment with combined high dosing of pyrazinamide and rifampicin to a selected group of patients with non-advanced pulmonary TB.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…11 Furthermore, data were recently presented on exposure-tolerability of 2 weeks treatment with rifampicin 40 mg/kg (n=15) and 50 mg/kg (n=17) where the dose of 40 mg/kg was safe and tolerable. 26 In early studies on lengthy treatments of pyrazinamide beyond 8 weeks, increased liver markers, jaundice and arthralgia were associated with higher doses of pyrazinamide. 51 In a meta-analysis comparing rates of AEs between different doses of pyrazinamide, the frequencies of hepatotoxicity were 0.042 (95% CI 0.026 to 0.067) for 30 mg/kg, 0.055 (95% CI 0.031 to 0.094) for 40 mg/kg and 0.098 (95% CI 0.047 to 0.193) for 60 mg/kg, suggesting a considerable proportion of hepatoxicity rates may be idiosyncratic rather than dose-dependent.…”
Section: Ethics and Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, rifampicin is highly protein-bound (6) and the cerebrospinal (CSF) penetration of total drug is poor (7), rarely exceeding the minimum inhibitory concentration of M. tuberculosis (8)(9)(10). Studies in pulmonary TB have shown that bactericidal activity is related to rifampicin area under the concentration-time curve (AUC) (11,12) and that microbiological outcomes are improved at higher doses, up to 40 mg/kg (13)(14)(15). A small randomized controlled trial showed survival benefit with the use of intravenous rifampicin 13 mg/kg for Indonesian adults with TBM (16), which had similar plasma exposures to oral rifampicin 20 mg/kg (17).…”
Section: Introductionmentioning
confidence: 99%